2011
DOI: 10.1016/j.scitotenv.2011.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemical amendment of dairy cattle slurry on phosphorus, suspended sediment and metal loss to runoff from a grassland soil

Abstract: Emerging remediation technologies such as chemical amendment of dairy cattle slurry have the 29 potential to reduce phosphorus (P) solubility and consequently reduce P losses arising from land 30 application of dairy cattle slurry. The aim of this study was to determine the effectiveness of 31 chemical amendment of slurry to reduce incidental losses of P and suspended sediment (SS) 32 from grassland following application of dairy cattle slurry and to examine the effect of 33 amendments on metal concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
3
33
0
2
Order By: Relevance
“…This shows that, especially for PL, using N contents for determining P rates might not be the best criterion. The reason is that, after successive manure applications, there was an accumulation of available P in the surface layers and migration in the soil profile, intensifying P transfer via surface runoff (Bertol et al, 2010;Ceretta et al, 2010b;Brennan et al, 2011;Kang et al, 2011) and leaching Girotto et al, 2013), which may cause eutrophication of surface and underground water bodies (Correll, 1998;Smith et al, 2007, Ceretta et al, 2010bHahn et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This shows that, especially for PL, using N contents for determining P rates might not be the best criterion. The reason is that, after successive manure applications, there was an accumulation of available P in the surface layers and migration in the soil profile, intensifying P transfer via surface runoff (Bertol et al, 2010;Ceretta et al, 2010b;Brennan et al, 2011;Kang et al, 2011) and leaching Girotto et al, 2013), which may cause eutrophication of surface and underground water bodies (Correll, 1998;Smith et al, 2007, Ceretta et al, 2010bHahn et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Soil moisture levels below or within +2% of field capacity (40.1%) By adhering to these criteria, the following spreading dates were adopted, thus ensuring that measurements encompassed the late winter and early spring periods: 7 December 2009, 18 January 2010, 1 March 2010 and 12 April 2010, with all intervals between spreading dates being 42 days. The runoff plots were established based on the methods detailed in the previous studies, including Brennan et al (2011), O Rourke et al (2012, McConnell et al (2013 a&b), Doody et al (2014) and McConnell et al (2015). Two weeks prior to each slurry application (so as to minimise soil disturbance), a shallow trench was excavated along the down-slope edge of each plot and a stainless steel V-shaped collection tray (0.5 × 0.1 × 0.1 m) placed in the trench to act as a runoff collector.…”
Section: Treatmentsmentioning
confidence: 99%
“…Thus the current study clearly demonstrates that during periods of high antecedent soil moisture levels the trailing-shoe technique can be equally effective as during the summer months in reducing the risk of P losses in runoff at this scale. A number of recent studies have examined measures to reducing the risk of P loss following slurry application to grassland soils under Irish conditions (O'Rourke et al, 2010;Brennan et al, 2011;O'Rourke et al, 2012;Serrenho et al, 2012;Murnane et al, 2015). For example, Brennan et al, (2011) reported an 86%, 83%, 69% and 67% reduction in DRP in runoff from soil boxes following the application of slurry amended with ploy-aluminium chloride hydroxide, alum, lime and FeCl 2 , respectively.…”
Section: Effect Of Slurry Treatment On P Losses In Runoffmentioning
confidence: 99%
See 2 more Smart Citations